If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2 + x)(x + 5) = 9x + -10 Reorder the terms: (-2 + x)(5 + x) = 9x + -10 Multiply (-2 + x) * (5 + x) (-2(5 + x) + x(5 + x)) = 9x + -10 ((5 * -2 + x * -2) + x(5 + x)) = 9x + -10 ((-10 + -2x) + x(5 + x)) = 9x + -10 (-10 + -2x + (5 * x + x * x)) = 9x + -10 (-10 + -2x + (5x + x2)) = 9x + -10 Combine like terms: -2x + 5x = 3x (-10 + 3x + x2) = 9x + -10 Reorder the terms: -10 + 3x + x2 = -10 + 9x Add '10' to each side of the equation. -10 + 3x + 10 + x2 = -10 + 10 + 9x Reorder the terms: -10 + 10 + 3x + x2 = -10 + 10 + 9x Combine like terms: -10 + 10 = 0 0 + 3x + x2 = -10 + 10 + 9x 3x + x2 = -10 + 10 + 9x Combine like terms: -10 + 10 = 0 3x + x2 = 0 + 9x 3x + x2 = 9x Solving 3x + x2 = 9x Solving for variable 'x'. Reorder the terms: 3x + -9x + x2 = 9x + -9x Combine like terms: 3x + -9x = -6x -6x + x2 = 9x + -9x Combine like terms: 9x + -9x = 0 -6x + x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-6 + x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-6 + x)' equal to zero and attempt to solve: Simplifying -6 + x = 0 Solving -6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + x = 0 + 6 x = 0 + 6 Combine like terms: 0 + 6 = 6 x = 6 Simplifying x = 6Solution
x = {0, 6}
| t=s-4/7 | | 4x-10=35 | | P=3*99+57 | | -3=-2/3z | | 9x+4=-8x+20 | | -22=-1(x-4) | | 9/10=x/50 | | 0=9(k-2/3)=33 | | (4/13^2)-(6/5y) | | 9/19=x/50 | | 2(k-4)=4(2k+1) | | 2(6x+1)=4(c-5)-2 | | 4y+6=2x | | 10x+15=12x+3-6-4 | | 4x-2(x-4)=-7+4x+11 | | 4b+2=2b-6 | | 4x+12y=172 | | 3x-4(2x)=0 | | 2r^3+3r+1=0 | | 3x-4(2x)=o | | 2*10^5/4*10^8 | | 10=-16t^2+75t+50 | | 16=32+8(y-4) | | 41-2x=29 | | -2=5g-7 | | 25-18.5=x | | c=a+1 | | 12c-4=56 | | 5x^2+30x+58=0 | | 4m-1=6m+7 | | 2x^2=35-3x | | 2B+10=12-B |